Evaluating the impact of shared situational awareness on combat effectiveness in symmetric engagements. (26th August 2021) - Khasawneh, Mahmoud T.; Shearer, Nevan; Rabadi, Ghaith; Bowling, Shannon; Jaradat, Raed
The information age combat model (IACM) is a popular representation of network centric operations (NCO). NCO is a military doctrine championed by the USA. This paper presents the results of a discrete event simulation (DES) of the IACM. The objective is to understand the impact of shared situational awareness on combat effectiveness in symmetric engagements. Symmetric in this context means the battle engagements studied involved units having an equal number of sensors, deciders, and influencers. After model verification, the results of the linear and nonlinear regression analyses will be presented and discussed. The analyses have been carried out on the aggregated data first and then the data was disaggregated to focus on high percentage win engagements and evenly-matched engagements. The focus will be on highlighting the utility of the performance metrics defined and used in previous IACM research studies.